(untitled) - Sole, Catherine L.

Distribution and phenotypic population structure of the tsetse flies Glossina morsitans morsitans Westwood and Glossina morsitans centralis Machado in Zambia (University of Pretoria, 2024)
Thesis (PhD (Entomology))--University of Pretoria, 2024.